THE REPRESENTATION OF SUMBA WOMEN IN THE FILM MARLINA THE MURDERER IN FOUR ACTS (AN ANALYSIS OF CHARLES SANDERS PIERCE) - Aulia Asmarani; Asep Hidayat (Dinasti Publisher, 2022)
Violence against women is still common in a modern era like today, not least for women who live in the rimland region. Women are often used as a violent objects by men. The patriarchal culture still embraced by some people makes it difficult for women to fight against male domination in their environment. This makes it difficult for women to fight against male domination in their environment. Especially for Sumba women, whose society still adheres to the patriarchal culture. The movie